2020
DOI: 10.3390/ijgi9020092
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Urban Spatial Structure Based on POI (Point of Interest) Data: A Case Study of the Central City of Lanzhou, China

Abstract: The study of urban spatial structure is currently one of the most popular research fields in urban geography. This study uses Lanzhou, one of the major cities in Northwest China, as a case area. Using the industry classification of POI data, the nearest-neighbor index, kernel density estimation, and location entropy are adopted to analyze the spatial clustering-discrete distribution characteristics of the overall economic geographical elements of the city center, the spatial distribution characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 32 publications
0
42
0
4
Order By: Relevance
“…Existing works have provided valuable knowledge on POI visit modeling for epidemic prediction [7], urban planning [16,25], recommendation [33,36] and other important applications. Chang et al [7] leverage the POI visit records to facilitate epidemic modeling.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Existing works have provided valuable knowledge on POI visit modeling for epidemic prediction [7], urban planning [16,25], recommendation [33,36] and other important applications. Chang et al [7] leverage the POI visit records to facilitate epidemic modeling.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…KDE is a useful method to estimate unknown density function in probability theory. It computes the density contribution of each sample point in the specified range to the centre point of each grid through the kernel function, and finally generate a smooth surface indicating the density map [52]. The amount of POI data in different categories varies greatly, for example, the number of POI data in commercial and business category are greater than the number in other categories.…”
Section: Identifying Building Functions Based On Kdementioning
confidence: 99%
“…If each POI site is regarded as a functional unit, then the higher the POI density, the more concentrated the urban functions in an area. POI kernel density analysis was made with ArcGIS software, which is often used to identify urban centers, economic vitalities, and intensities of human activities [55][56][57]. However, in the field of LSM, no research has been found when using POI as an influencing factor in human engineering activities thus far.…”
Section: Factors Of Human Engineering Activitiesmentioning
confidence: 99%